(untitled) (Research, Society and Development, 2020)
This study aimed to carry out an integrative literature review regarding social support and its importance for the rehabilitation of drug users. The Scielo and BVS databases were accessed through the descriptors "Social support" and "Drug users" with the help of the Boolean operator ’and’, adding the filters "last 5 years" and "Brazil" (2016- 2020). The search resulted in 08 articles, the content of which was organized into a single textual corpus, with similarity analysis and the construction of the word cloud. At the end, a qualitative content analysis was carried out, in order to seek to group the main contents explored by the literature. 74.5% were produced in the South and Southeast and 25% in the Northeast. Only one study carried out used quantitative statistics, the others were based on qualitative analysis with a smaller number of respondents. With regard to the population analyzed, 37.5% of the studies conducted the research directly with drug users, and 62.5% with other target audiences, including the users’ families, the health professionals who attended them, and a research focused on media analysis on the subject. Social support for the rehabilitation of drug users still needs more effective strategies, including greater training for professionals involved in the process, which should help to create opportunities for social reintegration and family support. Even in the face of some limitations, this support is essential to redefine the individual’s self-image in its entirety.